Physiological profiles of elite freestyle wrestlers - Callan, S. D.; Brunner, D. M.; Devolve, K. L.; Mulligan, S. E.; Hesson, J.; Wilber, R. L.; Kearney, J. T. (The Journal of Strength and Conditioning Research, 2000)
The U.S. Freestyle Wrestling Team was evaluated while in preparation for the 1997 World Championships. Athletes were tested on 6 physiological parameters: upper-body muscular power and endurance (5.6-m rope climb, RC, and 5-stage modified Wingate); body composition (BF%, skinfold measures); lower-body muscular power (vertical jump, VJ); upper-body power and anaerobic capacity (5-stage modified Wingate protocol); peak aerobic power (peak o2) using the treadmill or cycle ergometer; and lower back/hamstring flexibility (sit and reach). Blood lactate (HLa) measures were taken 2 minutes after the Wingate and peak o2 tests. Major results (mean ± SD) are as follows: BF% 7.6 ± 3.4; VJ (cm) 60 ± 10; RC (seconds) 9.3 ± 4.4; flexibility (cm) 3.8± 5.8. Mean peak o2, HLa, and heart rate results from the treadmill test were 54.6 ± 2.0 ml·kg1·min1, 15.1 ± 3.5 mmol·L1, and 186 ± 7.0 b·min1, respectively. Mean peak o2, HLa, and heart rate results from the cycle ergometer test were 41.2 ± 6.1 ml·kg1·min1, 10.6 ± 0.2 mmol·L1, and 176 ± 1.0 b·min1, respectively. For repetitions 1-5 of the upper-body Wingate test, peak power averaged 6.3, 4.7, 3.8, 3.5, and 3.5 W·kg body weight1, respectively. The fatigue indices for efforts 1-5 were 35.0, 33.2, 30.9, 29.4, and 31.6%, respectively. These results may provide a profile of elite freestyle wrestlers that can be used as training targets for developing athletes. The results may also provide information for training and tactical emphases.